Meningkatkan Penjualan UMKM sebagai Wujud Pemberdayaan Pada UMKM Bangun Jaya Di Desa Sukaraya - Ismamudi, Ismamudi; Dharma, Yuki Dwi (DPPM Universitas Pelita Bangsa, 2024)
Abstract The Micro, Small, and Medium Enterprises (MSME) sector plays a crucial role in shaping Indonesia's economic activity and serves as a fundamental pillar of the national economy. According to Law No. 20 of 2008, MSMEs refer to productive enterprises that are owned by people or corporate entities and fulfill certain conditions. The objective of this study is to investigate the Bangun Jaya banana bread micro, small, and medium enterprise (MSME) in Hamlet 1 Sukaraya Village, which is overseen by Pak Nedi. The study employs qualitative methodologies to comprehensively comprehend the operations of these micro, small, and medium enterprises (MSMEs). Comprehensive interviews, observation, and documentation acquired the data. The study findings indicate that Bangun Jaya's banana bread manufacturing system is commendable and sophisticated. However, there are still challenges in terms of marketing. The involvement of the Real Work Lecture team from Pelita Bangsa University enables the implementation of a more comprehensive marketing approach to boost sales of this product.